Spontaneous Interentity Coordination in a Dissipative Structure. Issue 1 (2nd January 2016) - Davis, Tehran J.; Kay, Bruce A.; Kondepudi, Dilip; Dixon, James A.
ABSTRACT: Humans and other creatures display remarkable interorganism coordination. For ecological theorists, interorganism coordination poses a challenge because it appears to be an especially "representation-hungry" phenomenon (Clark, 1999 ). Ecological researchers have proposed that interorganism coordination arises from fundamental laws of pattern formation and synchronization. A key example in support of the ecological approach to coordination is the phase locking of 2 or more weakly coupled metronomes. Here we provide a complementary example of interentity coordination in a system that is more closely analogous to living systems. We show that two self-organizing dissipative structures, coupled in a single electrical field, spontaneously exhibit fairly complex motion coordination. Further, the degree of coordination predicts the rate of entropy production for the system as a whole. We suggest that the complex behavior of motion coordination fulfills a rudimentary end-directedness of the system: evolve to states that create higher rates of entropy production.